Risk factors for criminal recidivism – a prospective follow-up study in prisoners with substance abuse - Håkansson Anders; Berglund Mats (BMC Psychiatry, 2012)
Abstract Background Substance use in general has been shown to predict criminal recidivism. The present study aimed to examine potential predictors of criminal recidivism, including substance-specific substance use patterns, in prisoners with substance use. Methods A cohort of prisoners with substance use problems (N = 4,152) were assessed with the Addiction Severity Index (ASI) in the Swedish criminal justice system. Clients were followed for an average of 2.7 years. Criminal recidivism was defined as any return to the criminal justice system. Results During follow-up, 69 percent (n = 2,862) returned to the criminal justice system. Recidivism was associated with amphetamine and heroin use, with an additive risk for injectors, and with polysubstance use. Also, recidivism was negatively associated with alcohol, other opioids than heroin/methadone and with hallucinogenic drugs, and positively associated with previous psychiatric in-patient treatment, violent behaviour, and with a shorter index sentence. Associations remained when controlling for type of crime. Conclusions Even when controlling for type and severity of crime, and for psychiatric problems, risk of criminal relapse was increased by substance use variables, including amphetamine, heroin and polysubstance use, and an additional risk was shown for injection drug users. These findings have implications for the need for substance abuse treatment after release from prison.